2021
DOI: 10.2139/ssrn.3785999
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of COVID-19 Patients in a Regional Population with Diabetes Mellitus: The ACCREDIT Study

Abstract: Objective: To identify clinical and biochemical characteristics associated with 7-& 30day mortality and intensive care admission amongst diabetes patients admitted with COVID-19.Research Design and Methods: We conducted a cohort study collecting data from medical notes of hospitalised people with diabetes and COVID-19 in 7 hospitals within the Mersey-Cheshire region from 1 January to 30 June 2020. We also explored the impact on inpatient diabetes team resources. Univariate and multivariate logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Despite the aforementioned literature in support of the findings of this present study, those who reported otherwise are worth noting. A study of 1004 diabetic patients with COVID-19 found that HbA1c or RBG was statistically associated with mortality [ 30 ]. Another study involving 3,295 COVID-19 patients found that HbA1c was associated with severe COVID-19, ICU admission, or all-cause mortality in both diabetic and non-diabetic groups [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the aforementioned literature in support of the findings of this present study, those who reported otherwise are worth noting. A study of 1004 diabetic patients with COVID-19 found that HbA1c or RBG was statistically associated with mortality [ 30 ]. Another study involving 3,295 COVID-19 patients found that HbA1c was associated with severe COVID-19, ICU admission, or all-cause mortality in both diabetic and non-diabetic groups [ 31 ].…”
Section: Discussionmentioning
confidence: 99%